A new social sciences network for infectious threats - Giles-Vernick, Tamara; Kutalek, Ruth; Napier, David; Kaawa-Mafigiri, David; Dückers, Michel; Paget, John; Ahmed, Syed Masud; Cheah, Phaik Yeong; Desclaux, Alice; De Vries, Daniel; Hardon, Anita; MacGregor, Hayley; et al. (The Lancet, 2022)
This article was published in The Lancet Infectious Diseases [© 2019 Elsevier Ltd. All rights reserved.] and the definite version is available at: https://doi.org/10.1016/S1473-3099(19)30159-8 The Journal's website is at: https://www.sciencedirect.com/science/article/abs/pii/S1473309919301598?via%3Dihub